OPTIMAL CAPITAL STRUCTURE ANALYSIS OF PT CENTRATAMA TELEKOMUNIKASI INDONESIA TBK - Zahriansyah, Rafly
PT Centratama Telekomunikasi Indonesia, Tbk has been significantly increasing their telecommunication tower portofolio every year since 2017, primarily through acquisition. In 2022, the company acquired approximately 4,000 telecommunication towers, propelling it to become the third- largest telecommunication tower provider in Indonesia. However, this debt-funded acquisition resulted in the interest expense to be higher than the EBIT, which causes the net income to be in the negative. The magnitude of this negative income exhausted the remaining equity from the company, resulting in a negative equity position. Recently, PT Centratama Telekomunikasi Indonesia, Tbk is planning to acquire an additional 397 telecommunication towers that will cost the company IDR 1.17 trillion. PT Centratama Telekomunikasi Indonesia, Tbk intends to finance this acquisition through a combination of internal cash and debt. This financing decision should be thoroughly assessed to ensure that PT Centratama Telekomunikasi Indonesia, Tbk is able to acquire funds with the least cost. The most favorable financing strategy can be assessed by calculating the optimal capital structure of the company to determine the lowest cost from the financing. This research will use the Weighted Average Cost of Capital method to determine the optimal capital structure. Based on the PT Centratama Telekomunikasi Indonesia, Tbk’s 2021 restated financial report, the company’s capital structure is currently at 38.14% equity and 61.86% debt which incurs cost of capital of 10.75%. Meanwhile, the optimal capital structure calculation suggested PT Centratama Telekomunikasi Indonesia, Tbk can achieve the lowest cost of capital at 9.08% with the proportion of equity and debt at 86% and 14%, respectively. Therefore, the most favorable financing strategy for the recent acquisition plan is by using equity to achieve the optimal capital structure.